The Role of Supervisory Support and Self-Efficacy on Work Effectiveness with Work Burnout as a Moderator Variable - Arif Rachman Putra; Didit Darmawan (Universitas Nusantara PGRI Kediri, 2024)
This study aims to investigate the effect of supervisory support and self-efficacy on work effectiveness, with work burnout as a moderating variable. The quantitative method was used using a questionnaire distributed to 100 respondents who worked at a company in Surabaya. The results of data analysis using the multiple regression method reveal that supervisory support has a significant positive impact on work effectiveness, along with self-efficacy which also has a significant positive influence on work effectiveness. Then supervisory support moderates the relationship positively and significantly towards work burnout. Self-efficacy was found to moderate the relationship positively and significantly to job burnout, indicating that the higher the level of self-efficacy, the lower the perceived level of job burnout. Meanwhile, work burnout negatively and significantly moderates the relationship to work effectiveness, indicating that the higher the level of work burnout, the lower the observed work effectiveness.